Normalized Difference Vegetation Index (NDVI) analysis for vegetation cover in Leuser Ecosystem area, Sumatra, Indonesia - Adisti Permatasari Putri Hartoyo; ARZYANA SUNKAR; RAHMATULLOH RAMADANI; SYAHLAN FALUTHI; SYAFITRI HIDAYATI (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Hartoyo APP, Sunkar A, Ramadani R, Faluthi S, Hidayati S. 2021. Normalized Difference Vegetation Index (NDVI) analysis for vegetation cover in Leuser Ecosystem area, Sumatra, Indonesia. Biodiversitas 22: 1160-1171. About 2 Mha of 24.3 Mha degraded area in Indonesia is inside conservation area. The Leuser Ecosystem Area (LEA) is the largest conservation area in Malesian forest that plays essential role in biodiversity and ecosystem services conservation efforts. It is the last habitat on earth where Sumatran tigers, elephants, orangutans, and rhinoceros are found together. However, LEA faces many threats, such as infrastructure development, and industrial palm oil plantation. Additionally, vegetation cover data as an approach to monitor forest cover changes in LEA is still lacking and baseline data regarding composition, structure as well as vegetation diversity in LEA is very limited. The objectives of this study were to analyze vegetation cover using Normalized Difference Vegetation Index (NDVI) in LEA and its relation to agroforestry structure, composition and diversity in Agusen Village, Gayo Lues District and Alur Durin Village, East Aceh District, Aceh Province belonging to LEA. Based on the NDVI analysis, the largest area in LEA belonged to class 5, meaning that the most area in LEA was dominated by high dense vegetation (1,870,116.40 ha). The average accuracy and standard error of NDVI analysis were 83.33% and 2.62. LEA is an effective buffer for maintaining forest ecosystems and increasing the local communities' welfare through agroforestry system. Agroforestry structures in agroforestry practices, both in Agusen Village and Alur Durin Village did not reflect reverse-J curve, meaning that enrichment planting for increasing numbers of individual and species was necessary. Management of agroforestry system depends on the landowners or managers and their selection of shade tree species with high economic value with market demand such as C. arabica, T. cacao with A. moluccanus, L. leucocephala, H. brasiliensis, D. zibethinus, etc. Trees that produce non-timber products are also an alternative way for conservation strategy and sustainable utilization.